Parametric modeling and simulation analysis of porous materials prepared by 3D printing technology - Li Tianhua; Ma Hailong; Xu Shubo; Liu Renhui; Pan Yuefei; Ren Guocheng; Li Jianing; Zhao Zhongkui (International Journal for Simulation and Multidisciplinary Design Optimization)
The study in this paper is the modeling as well as simulation analysis of porous materials prepared by 3D printing technique. The structural simulation analysis of porous material is carried out using ANSYS Workbench 15.0 to derive the deformation as well as stress distribution. Based on the simulation results the equivalent elastic modulus of the porous material is calculated under the homogenization theory. The effect of different parameters on the mechanical properties of the porous material is analyzed, and the most suitable model parameters are compared with the elastic modulus of human bone. The analysis results show that the main factor affecting the mechanical properties of porous materials is the porosity, and the secondary factor is the properties of the materials themselves. The nickel-based alloy tetrahedral porous material can reach the level of human cortical bone when the porosity reaches 70–87%, and the titanium alloy tetrahedral porous material can reach the range of 60–70% porosity. When the porosity of titanium alloy tetrahedral porous material reaches 87% level, it can reach the level of human cancellous bone.